Een inclusieve geschiedenis van een oorlog: Repliek - 't Hart, Marjolein (TSEG - The Low Countries Journal of Social and Economic History, 2025)
I would like to respond to the preceding reflections on my book Oorlog en ongelijkheid. Een inclusieve geschiedenis van de Gouden Eeuw. The debate focuses on growing inequality, caused by war-driven concentration of economic growth in the province of Holland at the expense of other provinces. Upper classes enriched themselves thanks to numerous war loans. Commoners paid the bulk of the war costs in taxation. Farmers suffered from strategic flooding and scorched earth campaigns, the peasantry above all. My inclusive history embraces stories of lower classes, women, refugees, and colonized peoples.